Inativação fotodinâmica de Staphylococcus aureus por ftalocianinas metálicas livres e encapsuladas em nanopartículas de PHB - Ferreira, Julyana Noval de Souza (2021)
One of the global problems that has been progressively growing in recent years and causing critical consequences for public health is antimicrobial resistance. Antimicrobial photodynamic therapy proposes an alternative to the use of antibiotics to treat localized infections. This technique combines a photosensitizer, a light source at a specific wavelength, and oxygen molecules, which together cause the formation of cytotoxic oxygen species. Phthalocyanines are compounds that have great potential as photosensitizers, however they have high hydrophobicity, requiring a carrier system to improve their capability as a therapeutic agent. This work proposed to investigate the efficiency of indium phthalocyanines containing the 7-oxo-3-(3,4,5- trimethoxyphenyl)coumarin substituent in non-peripheral (3NInOAc) and peripheral (4NInOAc) regions in the photodynamic inactivation of S. aureus bacteria sensitive (MSSA) and resistant (MRSA) to methicillin, considering the compounds free and encapsulated in PHB nanoparticles. For this purpose, the polymeric nanoparticles were prepared according to a 23 factorial design, and the photosensitizers photodynamic activity was also evaluated by the photooxidation of biomolecules (Trp and BSA). Theoretical calculations and molecular docking were performed to explain the entrapment efficiency of photosensitizers in PHB nanoparticles and the effectiveness in photooxidizing biomolecules. Encapsulated photosensitizers showed greater photodynamic efficiency than the free ones in the Trp photooxidation. However, encapsulation decreased the interaction of the photosensitizer with BSA, reducing the protein photooxidation. Phthalocyanine 4NInOAc, free and encapsulated, was more efficient than 3NInOAc in photooxidizing biomolecules and inactivating bacterias, although both photosensitizers were able to photooxidize Trp and BSA, as well as inactivating MSSA and MRSA. It is noteworthy that free phthalocyanines showed greater photodynamic efficiency than the encapsulated ones in reducing the bacteria viability, with the greatest inactivation obtained with the free 4NInOAc, whose reduction was 2.57 and 2.28 logs for MSSA and MRSA, respectively. The results revealed that both compounds, free and encapsulated, showed moderate antimicrobial action, reducing an average of 2 logs (99%) of MSSA and MRSA colonies.